Analisis Istihsan Atas Pertimbangan Hakim Terhadap Saksi Non Muslim Pada Perkara Perceraian - Misbahul Zaman (AL-HUKAMA, 2018)
Verification in the Religion Court is important because the court upholds law and justice based on no other evidence, including in civil cases, such as divorce. One of the proofs is a witness testimony. The majority of Islamic law experts like Imam Malik, Imam al-Shafi'i or Imam Ahmad ibn Hanbal agreed that a witness must be a Muslim, so that in a case witnessed by someone who is not Muslim, his testimony is deemed invalid. This article wants to see a case of establishing non-Muslim witnesses in a divorce case in the Sidoarjo Religious Court by using descriptive analysis, which is systematically describing the facts and characteristics of the object studied by the later analysis and using the istihsan theory. Based on the analysis, the Sidoarjo Religious Court in Case No. 1889/Pdt.G/2017/PA.Sda. has received the status of a non-Muslim witness because it has fulfilled formal requirements in a civil procedure law. In line with istihsan theory, non-Muslim testimony is permissible because of the development of the present era and its greater difficulties so that it can be accepted in religious courts. If it is forced that witnesses to be Muslim, then justice seekers will be harmed and have difficulties.